PENGARUH SOFT TQM TERHADAP KINERJA PERUSAHAAN DENGAN HARD TQM SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perhotelan di Purwokerto) - Tri Sekar Priyanti (Universitas Amikom Purwokerto, 2011)
This research is to develop a theoritical model about performance and to doan empirical test to know the influence of soft TeM toward performance with HardTpM as moderating by empiricar test in medium hotit iemice companv inPurwokerto. The research subject is CEo. The research population is I is ielatihotel service companies in Purwokerto. The research simpte is 90 melati hotelservice companies determined by spss for windows with Moderating RegresionAlnlysis. The conclution of the research are: soft TeM ( incrudes